Media Framing of Gender in the Cianjur 2022 Earthquake: A Social Work Perspective - Dwi Rahayu Nurmiati; Binahayati Rusyidi; Budi Muhammad Taftazani (INJECT (Interdisciplinary Journal of Communication), 2025)
Disasters often exacerbate existing gender inequalities, yet media representations rarely reflect this structural dimension. This study examines how mainstream Indonesian media framed gender issues following the 2022 Cianjur earthquake, using Entman’s framing theory through a social work perspective. A descriptive qualitative method was employed to analyze seven purposively selected online news articles using four framing dimensions: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The results reveal that women were predominantly portrayed as passive victims, with minimal acknowledgment of their agency or the structural causes of vulnerability. Media narratives emphasized emotional portrayals and short-term, charity-based solutions, while only one article offered a partial empowerment frame. These findings suggest that the media plays a critical role in shaping post-disaster gender narratives. The study concludes that integrating social work principles such as empowerment, justice, and inclusion into media analysis can inform more ethical and gender sensitive reporting practices, ultimately contributing to more equitable disaster recovery efforts